What deaf students from the Federal University of Santa Maria say about their conditions of study in higher education (Práxis Educativa, 2017)
This paper aims at describing some results from the investigation on how deaf students from the Federal University of Santa Maria, according to their own perception, have been assisted in their linguistic and pedagogical needs in the graduation courses. Their choice of this institution is due to the fact that it has a selection test for the Brazilian Sign Language (Libras, Brazilian Portuguese abbreviation) using video recording. This makes the institution have a greater number of deaf students when compared to other universities and creates an environment which is different from other university contexts. The study comprised descriptive and exploratory research; data collection was carried out through the application of an electronic questionnaire (online) to 18 deaf students. The results revealed that despite the differentiated access to this university, there are still many similarities when compared to other university contexts. The conclusions point out to the maintenance of precarious conditions for the permanence of these students in the classroom. Keywords: Deaf students. Higher Education. Permanence.